Solving Smartphone Storage Management Problems: Students’ Mathematical Literacy Based on Self-Regulated Learning - Aripin, Usman; Rosmiati, Tanti; Pitriyani, Widaningsih; Fauzi, Fikri (Edumatika, 2024)
The students’ mathematical literacy skills tend to be influenced by their self-regulated learning. This study aims to analyse mathematical literacy skills based on students' self-regulated learning. The research method used was descriptive-qualitative, involving 40 students from one of the Islamic junior high schools in Bandung Barat, West Java. The instruments used were a PISA-like mathematical literacy problem and a self-regulated learning questionnaire. The data analysis technique used was the Miles and Huberman model. This model uses data collection, data reduction, data presentation, and conclusion drawing. The results showed that students with high and medium level of self-regulated learning had given correct and careful answers related to managing storage on smartphones, but the students with a moderate level of self-regulated learning were careless in performing calculations. While, students with a low level of self-regulated learning have been able to understand the problem carefully, even though they have difficulty finding the right answer. This reseach can be used as one of basis for developing more effective learning strategies that support the improvement of mathematical literacy through empowering self-regulated learning.